2020
DOI: 10.3390/su12052001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Weather Factors on Thermal Comfort in Subtropical Urban Environments

Abstract: Urbanization has influenced the distribution of heat in urban environments. The mutual influence between weather factors and urban forms created by dense buildings intensify human perception of the deteriorating thermal environment in subtropics. Past studies have used real-world measurements and theoretical simulations to understand the relationship between climate factors and the urban heat island effect. However, few studies have examined how weather factors and urban forms are connected to the thermal envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…The seasons in Taiwan are divided into four. Winter runs from December to February, spring is from March to May, summer is from June to August, and autumn is from September to November [39], which is demonstrated from the data in Figure 5. This also shows that the summer season had the highest total irradiation and average module temperature, while the autumn season had the lowest.…”
Section: Evaluating the Performance Of Dmusmentioning
confidence: 73%
“…The seasons in Taiwan are divided into four. Winter runs from December to February, spring is from March to May, summer is from June to August, and autumn is from September to November [39], which is demonstrated from the data in Figure 5. This also shows that the summer season had the highest total irradiation and average module temperature, while the autumn season had the lowest.…”
Section: Evaluating the Performance Of Dmusmentioning
confidence: 73%
“…The ability of urban dwellers to adapt to varying thermal environments largely depends on the external meteorological conditions. However, considering temperature variations alone may not provide a comprehensive picture of the threats posed by heat stress; ambient relative humidity must also be considered as it influences the evaporation of sweat, which helps to naturally maintain human comfort levels (Huang et al., 2020; Qaid et al., 2016). Air temperatures between 18°C and 23°C and relative humidity (RH) levels between 35% and 70% are considered to be the comfortable ranges for livability (Höppe, 1999; Lin et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Based on relevant studies in Taiwan, relative humidity has a significant impact on apparent temperature, especially in subtropical regions. Higher relative humidity in cold weather makes people feel it is colder than the actual temperature ( 28 ), which may in turn lead to increased heater usage. One study in Romania also revealed direct association between humidity and the CO concentration in the environment ( 29 ).…”
Section: Discussionmentioning
confidence: 99%